Teoria da Tríplice Hélice: uma proposta de modelo de gestão estratégica aplicado à Agência de Inovação do Café (InovaCafé) - Costa, Cassio Henrique Garcia (2018)
The objective of this study is to create, through an action research, a model of strategic management for the Coffee Innovation Agency (InovaCafé), integrating the BSC to the theory of the Triple Propeller. The alignment of action research to Triple Propeller theory, Strategic Planning and the BSC approach provided the necessary inputs to the formulation of a strategic management model capable of contemplating the complexity of InovaCafé as an articulating organization of the Triple Propeller. With the development of a strategic map adapted to InovaCafé, the indicators, goals and initiatives are innovations that can be explored in other researches.